How to make critical decisions amid Covid-19 pressures - CHAN, David (Institutional Knowledge at Singapore Management University, 2020)
Time pressure and ambivalence are common when people make decisions in a crisis. Understanding the psychological dynamics helps us slow down to make better decisions.